A phantom for the quantitative determination and improvement of the spatial resolution in slice-selective 2D-FT magnetic resonance micro-imaging and -microscopy based on Deep X-ray Lithography (DXRL) - Berg, Andreas Georg; Börner, Martin (Frontiers in Physics, 2023)
The most important assessed quality-control (QC) criteria for improvements in high-resolution imaging are represented by the contrast-to-noise-ratio and spatial resolution. Ultra-High-Field (UHF) Magnetic-Resonance-scanners (B≥7T) for medical research allowed for the improvement in spatial resolution up to the microimaging and nominal microscopy range (pixel-size: ps<(100µm)2), even in-vivo on humans just recently. Preclinical MRI- and dedicated MR-microscopy (MRM) scanners already allow for microimaging and MRM (1-256 µm) but lack a sensible spatial resolution phantom for QC and performance improvements in hardware, pulse-sequencing and MR-protocols. In most scientific MRI articles, the spatial resolution is characterized by the ps, though this measurement parameter only limits the actual resolution. Here the Modulation-Transfer-Function (MTF) is used as evaluation concept for the determination of the spatial resolution in MRM using simple intensity profiles. The resolution limit is defined using a critical modulation-level. In approaching visual impressions on spatial resolution an additional criterion derived from the Modulation-depth-to-Noise-Ratio (MNR) is proposed. A practical method for assessment based on a concrete phantom design and its realization is shown. The phantom design consists of several sets of fine grids, specifically featuring high structural anisotropy for optimum SNR and CNR, with different spatial periods ranging from a1=256µm down to a8=2µm, not only for a quick visual qualitative check, but also for quantification of resolution using the MTF for two different spatial encodings in two orthogonal in-plane directions. The challenging demands on the manufacturing technology especially with regard to the aspect-ratio are approached using Deep-X-Ray-Lithography (DXRL) relying on the high brilliance of Synchrotron-irradiation. Smallest grid plates with width of 4µm corresponding to 125 line pairs/mm at a plate depth of 100µm were achieved. MR-microscopic images, originating from a microscopy-insert on a human UHF-MR-scanner, were used for demonstration of the evaluation process with two independent resolution-criteria. The developed prototype offers unique possibilities for quantitative resolution QC on UHF human and preclinical MR-scanners. Such a resolution-phantom might be very important for the improvement of MR-pulse sequences, MR-protocols and even hardware. In principle the phantom can also be used for other microscopic imaging-modalities as for instance µCT and Optical-Coherence-Tomography (OCT).